Two steps enhancement of dual mode (UC and DS) behaviour of Ho3+/Yb3+ and Tm3+/Yb3+ co-doped GdVO4 phosphors: Improvement in spectral and color purity - Dharendra K.; Roy A.; Dwivedi A.; Rai A.K.; Rai S.B.; Kumar D. (My University, 2025)
In the present work, the dual mode (Upconversion and Downshifting) emission behavior of Tm3+/Yb3+ and Ho3+/Yb3+ co-doped GdVO4 phosphors synthesized via high temperature solid state reaction technique have been studied. The pure phase formation has been confirmed by X-rays diffraction (XRD) studies. The crystalline nature has been found to improve on calcining the phosphors at 1473 K and also by incorporation of TiO2. The surface particles’ shape and size have been studied by SEM technique. The vibrational behaviour of the vanadate host has been investigated by Fourier Transform Infrared (FTIR) measurements. The UV–vis absorption spectra show the formation of charge transfer band (CTB) in UV region due to (VO4)3 group. The non-linear upconversion (UC) spectra show intense blue and NIR emission in GdVO4: Tm3+/Yb3+ phosphor on excitation with 980 nm radiation, whereas intense green and red UC emissions are observed in GdVO4: Ho3+/Yb3+ phosphor. The downshifting (DS) behaviour has been investigated in both the phosphors which show the self activation behaviour of GdVO4 host along with some sharp peaks in blue and green regions due to f-f transitions in Tm3+ and Ho3+ ions. The dual mode (UC and DS) emission has been further improved on heating the samples at higher temperatures and also by incorporation of TiO2. The color of the phosphor samples in the UC emission spectra has been visualized by CIE diagram. The color purity enhances in both the phosphors by increasing the calcination temperature and also by addition of TiO2. The spectral purity has been also calculated for the UC emission spectra and its also shows the same trend. Such phosphors are applicable for the display devices in blue, green and red regions via dual mode processes. © 2021 Elsevier Ltd